2011
DOI: 10.1016/j.ddmod.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The autodigestion hypothesis and receptor cleavage in diabetes and hypertension

Abstract: One of the key features of cardiovascular complications, such as hypertension or diabetes, is that they often appear at the same time in the same individual together with other forms of co-morbidities. While clinically a recognized phenomenon, no molecular mechanism for such co-morbidities has received universal acceptance. We propose a new hypothesis that provides a molecular basis for co-morbidities in hypertension due to unchecked proteolytic activity and receptor destruction. Testing of the hypothesis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Compared to its normotensive control, the Wistar Kyoto Rat (WKY), MMP levels, specifically MMP-2 and MMP-9, in the SHR are elevated (Chen et al, 2012; DeLano & Schmid-Schönbein, 2008; Tran et al, 2010), leading to ectodomain receptor cleavage and cellular dysfunctions (Chen et al, 2010; Delano et al, 2011; DeLano & Schmid-Schönbein, 2008; Rodrigues et al, 2010; Tran et al, 2010) generating its co-morbidities, such as insulin resistance. Levels of the endogenous tissue inhibitors of metalloproteinases (TIMPs), such as TIMP-1 and TIMP-2 with the ability to inhibit MMP-9 and MMP-2, respectively (Bernardo & Fridman, 2003; Brumann et al, 2012) are undetermined and will be presented in this report.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to its normotensive control, the Wistar Kyoto Rat (WKY), MMP levels, specifically MMP-2 and MMP-9, in the SHR are elevated (Chen et al, 2012; DeLano & Schmid-Schönbein, 2008; Tran et al, 2010), leading to ectodomain receptor cleavage and cellular dysfunctions (Chen et al, 2010; Delano et al, 2011; DeLano & Schmid-Schönbein, 2008; Rodrigues et al, 2010; Tran et al, 2010) generating its co-morbidities, such as insulin resistance. Levels of the endogenous tissue inhibitors of metalloproteinases (TIMPs), such as TIMP-1 and TIMP-2 with the ability to inhibit MMP-9 and MMP-2, respectively (Bernardo & Fridman, 2003; Brumann et al, 2012) are undetermined and will be presented in this report.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed increased MMP activity in plasma and different peripheral tissues, which indicated a general increase in protease activity in SHRs. MMPs are primarily responsible for extracellular matrix remodeling, and recent studies demonstrated that increased MMP activity produces receptor dysfunction due to the extracellular cleavage of several membrane receptors in hypertension, such as insulin, VEGFR-2 and β 2 -adrenergic receptors [17][18][19][20][21]. The The scale bar is 500 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a risk factor for mortality and morbidity [15,16]. Recent studies demonstrated that increased proteinase activity, including matrix metalloproteinases (MMPs), may be important in the loss of cellular function and end-organ damage in hypertension [17][18][19][20][21]. Clinical data support a role for plasma MMP-2 and MMP-9 levels as novel predictors of cardiovascular risk [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathology is the main cause of visual impairment in the population of economically developed countries [1][2][3][4]. It should be noted that even with the compensation of carbohydrate metabolism, the development of DR continues, so hyperglycemia is not the only factor in the development of retinopathy in diabetes [5][6][7][8][9]. To date, the key role of endothelial dysfunction in the occurrence and progression of DR has been proven [10,11].…”
Section: Introductionmentioning
confidence: 99%